2010
DOI: 10.1080/00914037.2010.504147
|View full text |Cite
|
Sign up to set email alerts
|

Poly(acrylamide-chitosan) Hydrogels: Interaction with Surfactants

Abstract: Semi-interpenetrating hydrogels were prepared from hydrophilic acrylamide and cationic natural biopolymer chitosan, N,N 1 -methylenebisacrylamide and water-soluble redox initiating system (ammonium persulfate=N,N,N 1 ,N 1 -tetramethylethylenediamine). The interaction of these hydrogels with different surfactants such as sodiumdodecylsulphate (SDS, anionic), N-cetyl N,N,N-trimethyl ammonium bromide (CTA, cationic) and Tween20 (T20 non-ionic) was studied. The chemical structure of the hydrogels treated with surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This particular hydrogel composition has its maximal sensitivity and linearity between pH 4 and 6 [3]. However, this range can be shifted to physiological pH levels by changing the ionizable monomer [9]. In this range, the sensor exhibited a sensitivity of 0.01 Oe/pH and a resolution of 0.05 pH unit.…”
Section: Figure 6: Cross Sectional Optical Photographs Showing the Hymentioning
confidence: 98%
“…This particular hydrogel composition has its maximal sensitivity and linearity between pH 4 and 6 [3]. However, this range can be shifted to physiological pH levels by changing the ionizable monomer [9]. In this range, the sensor exhibited a sensitivity of 0.01 Oe/pH and a resolution of 0.05 pH unit.…”
Section: Figure 6: Cross Sectional Optical Photographs Showing the Hymentioning
confidence: 98%
“…Formation of hydrogel of 1 (9.0 mm) proceeded in the presence of sodium octyl sulfate (5) in the concentration range 20-30 mm (samples 9-11). Sodium decyl sulfate (6) solutions showed similar behavior to SDS (2), with 0.25-5.0 mm solutions giving hydrogels with 9.0 mm of 1 (samples [12][13][14][15][16]. Sodium tetradecyl sulfate (7) solutions only formed hydrogels of 1 (9.0 mm) at low concentrations (0.10-1.0 mm; samples [17][18][19][20].…”
Section: Ionic Surfactants Induce Amphiphilic Trisa C H T U N G T R Ementioning
confidence: 99%
“…[10] Many studies on the effects of surfactants on polymer gels have been reported, and it is clear that electrostatic and hydrophobic interactions influence their swelling and shrinking. [11][12][13][14][15][16] However, studies on the effects of surfactants on the formation of supramolecular gels are limited. [17,18] We recently developed amphiphilic trisA C H T U N G T R E N N U N G (urea) LMWHGs.…”
Section: Ionic Surfactants Induce Amphiphilic Trisa C H T U N G T R Ementioning
confidence: 99%
“…Growing interest in these polymers result from their unique properties including great water absorption capacity, flexibility, or the possibility of their modification with various active substances which may be further release to the application site [5]. Importantly, both hydrogels based on natural materials such as chitosan [6], gelatin [7] or arabic gum [8] and synthetic ones, i.e. poly(vinyl alcohol) [9] or acrylic acid [10] are widely applied.…”
Section: Introductionmentioning
confidence: 99%